SISTEM PENDETEKSI KETERSEDIAAN DAN LOKASI TEMPAT DUDUK PADA RUANGAN MENGGUNAKAN MOVABLE PASSIVE INFRA RED (PIR) ARRAY - Ari Wibowo; Sri Arttini Dwi Prasetyowati; Suryani Alifah (Elkom : Jurnal Elektronika dan Komputer, 2022)
Based on statistical data, every year there is an increase in population. This also happened to the increasing number of Catholics. The increase member in Saint Aloysius Church of Mojosongo isn’t accompanied by an increase of seating facilities, to solved this, a device was designed which will show seats that have been used or still empty through a viewer that will be placed near the entrance. The research method used in this study is a quantitative method. The number of seats used by in one block is 25 seats, the seat sample is 9 seats. Three (3) PIR sensors are placed above the row to the seat 2, where the direction of the PIR sensor is drived by a stepper motor with an angle is 22.61°. Detection alternated and sequentially starting from row A, row B and row C. In general, the seat detection system based on ATMEGA16 works according to the design. People can find an empty seat position by looking at the viewer (LED) and looking for LED lights that are not lit.